Erythrocytic changes in patients with Systemic Lupus Erythematosus - Marilia B. P. Matos; Eliane P. Dias; Augusto C. Arruda; Nestor A. Aguiar Junior; Marcial F. Galera; Cristhiane A. Leite (Medicina, 2016)
Objective: We assessed the prevalence of erythrocytic changes in patients with SLE, at Cuiabá University General Hospital (UNIC-HGU). Methods: blood samples from 40 female patients were collected and processed (ABX Pentra 80 automation – flow cytometry). Descriptive statistical analyses were performed using IBM SPSS 2.0 statistical software. Results: 42.5% of the 40 patients showed lowered concentrations of hemoglobin. The hematocrit and hemoglobin dosage averages of the anemic patients were respectively of 29.7% and 9.9 gdL, while those without anemia showed 41.1% of hematocrit average and hemoglobin average dosage of 13,7gdL. Normocytic and normochromic anemia was the most prevalent, founded in 64.7% of the anemic patients, with normal hematimetric indices. In cases of macrocytic anemia, hematimetric changes, such as increased RDW, policromasy and reticulocytosis observed in some patients suggest hemolytic processes, commonly observed in these patients. Conclusion: Anemia was found in 42% of the patients and careful observation of the erythrocytic changes is an important tool in the follow up of LES patients